Isolation and Antibiotic Resistance Profile of Klebsiella spp. from the Gastrointestinal Tract of Broiler Chickens in Poultry Farms in Bali (Advances in Tropical Biodiversity and Environmental Sciences, 2025)
The poultry sector in Bali has experienced substantial growth, accompanied by a notable increase in broiler chicken populations. Information on Klebsiella spp. outbreaks in Bali has not yet been studied, despite the many potential infectious diseases that may affect broiler chickens on a large scale. Klebsiella spp. is an opportunistic pathogen that can induce severe respiratory disease in poultry, carrying a potential risk of zoonotic transmission. Furthermore, the increasing incidence of antibiotic resistance among Klebsiella strains poses a critical challenge to effective therapeutic interventions. This study was conducted to isolate and identify Klebsiella spp. from the gastrointestinal tract of broiler chickens in commercial farms across Bali, and to assess the antimicrobial resistance profiles of the isolates against multiple antibiotic agents. A cross-sectional study with a total of 25 cloacal swabs was conducted, and the swabs were subjected to microbiological analysis. Isolation was performed using selective MacConkey Agar (MCA), followed by Gram staining, biochemical identification, and antibiotic susceptibility testing through the Kirby-Bauer disk diffusion method. Two out of 25 (8%) samples were positively identified as Klebsiella spp. All of these positive isolates showed complete resistance to ampicillin, sulfamethoxazole, erythromycin, ciprofloxacin, and tetracycline. Additionally, the positive isolates also exhibited intermediate resistance against kanamycin, while 50% of the isolates demonstrated susceptibility to chloramphenicol. These findings confirm the presence of multidrug-resistant (MDR) strains among the isolates examined. The outcomes of this research emphasize the urgent need for a rigorous study to identify potential outbreaks caused by Klebsiella spp., throughout commercial farms in Bali and stringent monitoring and regulation of antibiotic usage within the poultry industry to mitigate the proliferation of antimicrobial resistance, thereby safeguarding animal health and preventing potential risks to public health.
Keywords: Antimicrobial resistance; Bali; Broiler Chickens; Multidrug ressistant; Klebsiella spp.